ChemInform Abstract: Capture of 3‐Amino‐4‐oxycyanofurazan and Characterization of Isoxazole Product. Issue 39 (5th September 2013) - Luo, Yifen; Wang, Bozhou; Zhang, Guofang; Zhou, Yanshui; Lian, Peng
Abstract Nitrile oxide (II) is assumed to be the reactive intermediate in the formation of (III) by dimerization or in the reaction with alkynes (IV) to give (V).